2000
DOI: 10.1007/bf03019478
|View full text |Cite
|
Sign up to set email alerts
|

Emergency management of deeply comatose children with acute rupture of cerebral arteriovenous malformations

Abstract: REPORTS O F INVESTIGATIONCAN J ANESTH 2000 / 47: 8 / pp [758][759][760][761][762][763][764][765][766] Purpose: To assess the impact of emergency management on mortality and morbidity of acute rupture of cerebral arteriovenous malformations resulting in deep coma in children, and the factors predicting outcome. Methods: Retrospective chart review of 20 children with a Glasgow Coma Scale # 8 with acute hemorrhagic stroke from a cerebral arteriovenous malformation rupture was conducted. Protocol included: early r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 32 publications
1
36
0
Order By: Relevance
“…Kuhmonen et al [7] reported 49 patients with ruptured bAVMs, aged between 2 months and 78 years, and showed that clinical outcome correlated significantly with the Hunt and Hess grade, intraventricular hemorrhage and age; however, it appeared that patients with poor conscious levels were distributed among groups of good and poor outcomes; thus a single parameter such as conscious level is not informative enough in daily clinical practice. Similar results appeared in another two reports [2,9]. We also encountered a similar problem when a single parameter or a single existing scoring scale was evaluated (table 3; fig.…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…Kuhmonen et al [7] reported 49 patients with ruptured bAVMs, aged between 2 months and 78 years, and showed that clinical outcome correlated significantly with the Hunt and Hess grade, intraventricular hemorrhage and age; however, it appeared that patients with poor conscious levels were distributed among groups of good and poor outcomes; thus a single parameter such as conscious level is not informative enough in daily clinical practice. Similar results appeared in another two reports [2,9]. We also encountered a similar problem when a single parameter or a single existing scoring scale was evaluated (table 3; fig.…”
Section: Discussionsupporting
confidence: 68%
“…In the literature, clinical outcome of patients with ruptured bAVMs with respect to patients’ admission condition has been discussed in several reports [5,6,7,9], but information about prognostic parameters applicable to daily clinical practice is still lacking. Kuhmonen et al [7] reported 49 patients with ruptured bAVMs, aged between 2 months and 78 years, and showed that clinical outcome correlated significantly with the Hunt and Hess grade, intraventricular hemorrhage and age; however, it appeared that patients with poor conscious levels were distributed among groups of good and poor outcomes; thus a single parameter such as conscious level is not informative enough in daily clinical practice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…34 Furthermore, it has been studied widely in the same experimental contexts as starches 24 and has been in clinical use for many decades. 35,36 Normal saline, one of the most commonly used solutions, was not chosen as a control because its volume effect is not comparable with that of colloids, given that it is easily lost from the intravascular space and, therefore, does not act effectively as a volume expander. The distribution among the three compartments (intravascular, extracellular, and intracellular) depends highly on the concentration of sodium.…”
Section: Discussionmentioning
confidence: 99%
“…Urgent surgery was undertaken given the patient's rapidly declining level of consciousness, and because of extensive intraoperative blood loss, a clip was placed on a middle cerebral artery (MCA) AVM feeder to gain hemorrhage control. Decompressive craniectomy and prolonged intracranial pressure monitoring with sedation were performed 15 following intracerebral clot evacuation, but AVM resection was not attempted by the attending neurosurgeon. After a prolonged intensive care unit stay, she made a good recovery and had only mild contralateral hemiparesis (Table 2) prior to definitive AVM surgery 12 weeks later.…”
Section: History and Examinationmentioning
confidence: 99%